Methodical bases and models of realization of the internal diagnostic systems at the engineering enterprises (Journal of Economic Research & Business Administration, 2016)
The world economic crisis, the instability of a political situation, the emergence of the new centers of economic development, the reorientation of the consumption markets, rupture of old economic relations have put before the engineering enterprises the requirements concerning the development of their own closed-cycle production, the search of new sales markets, the transition to the new international quality standards. Also, a need to improve the research processes of financial and economic activities and to increase their productivity has appeared that will lead to improvements in profitability, efficiency of enterprises. Considering the above, the article is devoted to theoretical and practical approaches functioning of the internal diagnostic systems at the engineering enterprises as an effective process of research activities of such entities. For this purpose, methodical bases of the researched process reveal. Besides, in the work separate models of internal diagnostic systems are considered and the own model, which is based on cost-income approach is proposed. This model means research of the factors reducing the net profit of the enterprise.
Keywords: system; internal diagnostics; model; financial and economic activity; formalization; result; method.